Applications of Multi-Contrast Optical Coherence Tomography in Assessment of Dysplastic Nevi to Malignant Melanoma - Lai, Pei-Yu; Shih, Tai-Yu; Chang, Chung-Hsing; Kuo, Wen-Chuan (Frontiers in Physics, 2022)
Melanoma is fatal for skin cancer. One of the essential predictive points in melanoma progression is the development of dysplastic nevi. This study observes subcutaneous blood vessels, lymphatic vessels, and skin thickness in a mouse model of dysplastic nevi in vivo through noninvasive, high-resolution, and multi-contrast optical coherence tomography (MCOCT). The subcutaneous microenvironment of the mice showed increased density of lymphatic vessels, dilated walls, and increased thickness of ears during the change of dysplastic nevi; and fragmentation of blood vessels at the later stage of the experimental period. Compared with conventional OCT only provides structure anatomy, MCOCT provides more in-depth information for disease analysis and has the potential to detect progressive changes in dysplastic nevi.